Legal Aspect of Cyber Notary in Indonesia - Luh Anastasia Trisna Dewi (Journal of Digital Law and Policy, 2021)
The urgency of cyber notary supposed to be a priority nowadays. Business transactions that use offline notary services have now penetrated online in line with technological developments and also the need for effective and efficient transactions. This article was compiled to find out various legal aspects that can support the legality of online notary activities. The method used to compile this article is the literature study method. The literature study method collects several primary, secondary and tertiary materials as a reference in the preparation of this article. Based on the literature study conducted, it can be concluded that the main duties and functions of a notary cannot be replaced directly with an information system. A gradual transformation is needed so that the concept of a cyber notary can run optimally.